Avaliação da interação entre o papilomavírus bovino e a célula hospedeira - Melo, Thatiana Correa de [UNIFESP] (2015)
Bovine papillomaviruses (BPVs) are oncogenic virus, with epithelium and mucous tropism, associated to benign lesions which can progress to malignancy, principally in presence of the environmental co-factors. Currently, there are 13 types of BPV described, classified in three genres: Delta, Epsilon and Xipapillomavirus. Objectives: This study aimed to identify the interaction between the BPV with primary cell cultures, as well as the virus with peripheral blood cells from bovines infected by BPV with different clinical characteristics of bovine papillomatosis. The viral activity was evaluated through the BPV proteins expression, morphological alterations and levels of clastogenicity. Methods: Samples of peripheral blood and tissue were collected from bovines uninfected by BPV, as well as, animals with cutaneous papillomas, esophagus and urinary bladder papillomas. The tissue samples were submitted to histopathological analysis and BPV detection. Primary cell cultures of each tissue sample were stablished and submitted to the investigation for lineage characterization by morphology, cytoskeletal (vimentin, cytokeratin, E-cadherin, ?-cathenin and actin), focal adhesion (vinculin), expression of E7 oncoprotein, replication (E2 e E1^E4) and capsid protein (L1) of BPV. Cell circle alterations, the levels of clastogenicity and the virus particle presence were analyzed in these systems. Results and Discussion: the presence of viral DNA, in episomal state, was detected in the passages of cell culture (P1-P6). Furthermore, the viral proteins expression was detected by RT-PCR, immunofluorescence and flow cytometry. Oncoprotein E7 was identified in cytoplasmatic region, the E2 and E1^E4 proteins were identified in the nucleus and cytoplasm and the L1 protein was present in nuclear and perinuclear region of culture cell and peripheral mononuclear cells (PBMCs). These same proteins were detected in paraffined tissue, being observed in epithelium and dermis. High levels of clastogenicity were identified both in cell culture and PBMCs in all groups of animals with papillomas, but not detected on uninfected bovines. Electron microscopy analysis showed the presence of structures very similar to virus particles. Culture cells from animals infected by BPV showed double labeling of vimentin/cytokeratin and alteration in the labeling standard of E-cadherin and ?-cathenin. Specifically, ?-cathenin was expressed in the cytoplasm and nucleus. These data suggest that these cells could be suffering an epithelial-mesenchymal transition (EMT). The EMT is responsible for the invasion/migration of cells with transformed phenotype, contributing to the metastasis genesis. Furthermore, the culture cells infected by BPV showed nuclear and depolarized F-actin. The protein was retracted in the cellular matrix. The presence of lamelipoids was detected. Probably, these alterations are result of viral protein activity. Conclusion: DNA virus presence in the passages, morphologic alterations and clastogenicity, as well as, the presence of BPV particles and protein expression represent strong evidences that the virus is active, occurring virus assembling in vitro. Alterations in cytoskeleton proteins and co-expression of proteins of epithelial and mesenchymal origin point out that the culture cells are suffering neoplastic modifications, characterized by EMT.